2018
DOI: 10.1177/1521025118774932
|View full text |Cite
|
Sign up to set email alerts
|

On-Campus Social Support and Hope as Unique Predictors of Perceived Ability to Persist in College

Abstract: The psychological construct of hope, characterized by goal-directed thinking rooted in personal agency and the ability to develop pathways to achieve goals, has long been demonstrated to predict academic success. A sample of 994 undergraduates participated in this study to better understand the role of hope and on-campus social support in predicting students’ perceived ability to persist and succeed in college. Results demonstrated that on-campus support, particularly from teachers and professors, significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…The shift to manifest variables using regression analyses was reasoned to allow for increased interpretability of demographic moderators (Little et al, 2007) and to align with our exploratory approach wherein we did not approach the CC and well‐being relationship with a specific theory (conversely, the use of latent CC and well‐being variables via structural equation modeling would need to be predicated on clear theoretical relationships between variables, see Cohen et al, 1990). Moreover, we used anxiety and hopefulness measures routinely assessed as manifest variables, thus aligning with the broader study of these phenomena (e.g., anxiety: Ganson et al, 2021; Liu et al, 2021; hopefulness: Bryce et al, 2020; D'Amico Guthrie and Fruiht, 2020) Significant interactions were probed using simple slope analysis (Aiken et al, 1991) one standard deviation at, below and above the mean using emtrends (Lenth, 2018). All regressions controlled for disability status, as ableism acts as a force affecting youth (Fine, 2019), and household income, since lower SEP is associated with increased critical action (Roy et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…The shift to manifest variables using regression analyses was reasoned to allow for increased interpretability of demographic moderators (Little et al, 2007) and to align with our exploratory approach wherein we did not approach the CC and well‐being relationship with a specific theory (conversely, the use of latent CC and well‐being variables via structural equation modeling would need to be predicated on clear theoretical relationships between variables, see Cohen et al, 1990). Moreover, we used anxiety and hopefulness measures routinely assessed as manifest variables, thus aligning with the broader study of these phenomena (e.g., anxiety: Ganson et al, 2021; Liu et al, 2021; hopefulness: Bryce et al, 2020; D'Amico Guthrie and Fruiht, 2020) Significant interactions were probed using simple slope analysis (Aiken et al, 1991) one standard deviation at, below and above the mean using emtrends (Lenth, 2018). All regressions controlled for disability status, as ableism acts as a force affecting youth (Fine, 2019), and household income, since lower SEP is associated with increased critical action (Roy et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Social support and hope predicted higher self-efficacy among college students with learning disorders (Mana et al, 2021). On-campus social support and hope have both been found to be related to ability to persist in college (D'Amico et al, 2018). Chang et al (2019) identified hope and social support as an effective adjustment mechanism of resilience to racial discrimination.…”
Section: Hopeful Thinkingmentioning
confidence: 96%
“…Meanwhile, the association between hope and social support has been established in prior studies. For example, hope and perceived social support were positively related among Chinese children with ADHD [ 43 ], and hope and social support were related to the ability to persist in college [ 44 ]. In addition, hope and social support were identified as an effective adjustment mechanism of resilience to racial discrimination [ 45 ].…”
Section: Introductionmentioning
confidence: 99%